Yoga bear : yoga for youngsters - Pierce, Karen Behan, 1964-; Brinkman, Paula (Chanhassen, MN : NorthWord Press, 2004)
Presents twenty-two poses that teach yoga to children through the use of rhyming word play and illustrated photographs that imitate animals and nature.
Horn Book
Library Media Connection
1.9
K-3.
K-3
Keywords: Hatha yoga for children -- Juvenile literature; Yoga; Yoga